Preparation method of sinter-free high-reflectivity ceramsite with solidified heavy metal

By using alkaline solid waste to stimulate the slag in the preparation of ceramite and performing high-temperature maintenance, the problems of complex sintering method and difficult to control the quality of ceramite in the existing ceramite preparation technology are solved, and sintering-free ceramite with high reflectivity and heavy metal curing performance are achieved.

CN118479903BActive Publication Date: 2025-03-14YANSHAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410577346.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2025-03-14
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

The existing ceram preparation technology has problems such as complex sintering method treatment, high fuel consumption and difficult to control the quality of ceram.

Method used

Alkaline solid waste is used instead of strong alkali exciters, and waste incineration fly ash and calcium carbide slag provides an alkaline environment, stimulates the slag, and promotes the hydration process through high temperature curing to prepare sinter-free ceramics with high reflectivity and heavy metal curing properties.

Benefits of technology

The high reflectivity and heavy metal curing properties of the ceramic particles are achieved, and the reflectivity of ultraviolet, visible and near-infrared light is improved through the composite structure, ensuring the stability of the ceramic particles and avoiding dust and stains.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118479903B_ABST
    Figure CN118479903B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of solid waste resource utilization, and a method for preparing a sinter-free high-reflectivity ceramsite with solidified heavy metals is provided, and the specific steps are as follows: slag, fly ash, carbide slag powder, sludge powder, shell powder and titanium dioxide are placed in a dry powder mixing and stirring machine in sequence to obtain a dry powdered mixture; a certain amount of dry powdered mixture is taken and placed in a disc granulator, and a mixed solution is sprayed on a ball core, and a dry powdered mixture and a mixed solution are repeatedly added to the disc granulator to obtain a spherical raw material; the spherical raw material is placed on a rolling disc, and an anti-radiation coating is sprayed to obtain a raw material ball with a spray thickness of 0.4-0.8mm; a super-hydrophobic surface with a thickness of 0.4-0.8mm is sprayed on the raw material ball to obtain ceramsite; ceramsite is cured in a water bath curing box and a curing room in sequence to obtain sinter-free ceramsite. The present invention excites slag and shell powder by physical activation, saline-alkali activation and thermal activation to prepare sinter-free ceramsite with solidified heavy metals and high reflectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste resource utilization, and in particular to a method for preparing sintering-free high-reflectivity ceramsite with solidified heavy metals. Background Art

[0002] Ceramic aggregate is a man-made lightweight aggregate, usually in the form of beads or porous particles, with the characteristics of light weight, high strength, and low water absorption. At present, as an important component of filter materials, more attention is paid to the adsorption performance of ceramsite. As a substitute for natural coarse aggregate, ceramsite is an excellent building material.

[0003] In the prior art, for example, CN 114956782 provides a method for preparing high-strength aggregate ceramsite using electroplating sludge, wherein the weight distribution ratio is 40-70 parts of electroplating sludge, 30-60 parts of siliceous material, and 5-15 parts of water; the obtained mixture is passed through a ball-forming disk or an extrusion granulator, and is shaped into spherical or columnar raw material balls, and the raw material balls are calcined to make finished ceramsite. The calcination method used in this application has high strength for manufacturing ceramsite, but the sintering method preparation technology has complex processing procedures, and the quality of ceramsite is not easy to control.

[0004] The existing ceramsite preparation technology usually adopts sintering method and cold bonding method to granulate. This process mainly uses calcined shell powder, titanium dioxide powder and industrial solid waste powder to make all-solid waste ceramsite through a granulator. This process is complicated and consumes a lot of fuel.

[0005] The invention uses alkaline solid waste to replace a strong alkali activator to prepare ceramsite, and waste incineration fly ash and carbide slag provide an alkaline environment to activate slag, and high temperature curing can promote the hydration process, and high temperature curing can promote C-(A)-sh gel, fill pores, and increase the compactness of the structure. Then, ceramsite with high reflectivity and heavy metal curing performance is obtained through special treatment. The ceramsite prepared by the invention has excellent curing performance for heavy metals in industrial solid waste, and the ceramsite adopts a composite structure to have excellent reflection performance for ultraviolet light, visible light and near infrared light. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a method for preparing sintering-free high-reflectivity ceramsite with the function of solidifying heavy metals. The method comprises the following steps: using slag and shell powder as matrix raw materials, wherein the shell powder improves the initial curing temperature and adsorption function of the ceramsite during the reaction, and using carbide slag, waste incineration fly ash and sodium silicate as activators. A dry powder mixture and a mixed solution are mixed by a disc granulator to obtain spherical raw materials. An anti-radiation coating and a super-hydrophobic coating composed of polystyrene, vinyl acetate, acetone, water and a defoaming agent are sequentially coated on the spherical raw materials, thereby improving the high reflectivity of the ceramsite to a reflectivity of more than 95%. The stability of the ceramsite performance is ensured, and dust and stains are prevented from contaminating the surface of the ceramsite, so as to obtain sintering-free ceramsite with the function of solidifying heavy metals and adsorbing phosphates.

[0007] The present invention provides a method for preparing sintering-free high-reflectivity ceramsite with solidified heavy metals, and the specific implementation steps include:

[0008] S1, subjecting the carbide slag slurry to static stratification to obtain a carbide slag lower slurry and a carbide slag upper clear liquid;

[0009] S2, placing the lower slurry of the carbide slag obtained in step S1 into a drying oven at a temperature of 50-60° C. to dry to constant weight, and grinding it with a ball mill to obtain carbide slag powder; drying and concentrating the carbide slag supernatant obtained in step S1 to obtain a carbide slag supernatant with precipitated crystals;

[0010] S3, adding 0.1 mol / L sodium carbonate solution into the carbide slag supernatant with precipitated crystals obtained in step S2 to obtain a mixed solution;

[0011] S4, placing the sludge in a drying oven at a temperature of 50-60°C to dry to constant weight, grinding it with a ball mill and passing it through a square hole sieve to obtain sludge powder;

[0012] S5, placing the shells in a drying oven at a temperature of 60° C. to dry to constant weight, and grinding them with a ball mill to obtain shell powder;

[0013] S6, placing the shell powder obtained in step S5 into a muffle furnace at a temperature of 1000-1200° C. for calcination to obtain calcined shell powder;

[0014] S7, placing slag, fly ash, carbide slag powder, sludge powder, calcined shell powder and titanium dioxide in a dry powder mixer in sequence to obtain a uniformly mixed dry powder mixture;

[0015] S8, placing the dry powder mixture obtained in step S7 in a disc granulator, and spraying the mixed solution obtained in step S3 onto the formed spherical core, and repeatedly adding the dry powder mixture to the disc granulator and spraying the mixed solution until a spherical raw material with a particle size of 5-10 mm is obtained;

[0016] S9, stirring polystyrene, vinyl acetate, acetone, water and defoaming agent in a 60° C. water bath for 1-2 hours to obtain an anti-radiation coating;

[0017] S10, placing the spherical raw material obtained in step S8 on a rolling disc, and spraying anti-radiation coating until a raw material ball with a spraying thickness of 0.4-0.8 mm is obtained;

[0018] S11, the raw material ball obtained in step S10 is subjected to a prefabricated nanoscale micro-convex structure, and a super-hydrophobic coating is sprayed on the raw material ball to obtain a super-hydrophobic surface with a spraying thickness of 0.4-0.8 mm, and the raw material ball is allowed to stand at room temperature for 24 hours to obtain ceramsite;

[0019] S12, placing the ceramsite obtained in step S11 in a water bath curing box at a temperature of 40-70° C. for curing for 8-14 hours, then taking it out and placing it in a curing room for curing to obtain sintering-free high-reflectivity ceramsite with solidified heavy metals.

[0020] Preferably, in step S3, the sodium carbonate in the sodium carbonate solution promotes the dissolution of OH-, and the specific chemical expression is:

[0021] Na2CO3+Ca(OH)2→2NaOH+CaCO3

[0022] 6NaOH+2H2O+4CaCO3→3Ca(OH)2+Na2Ca(CO3)·2H2O+2Na2CO3.

[0023] Preferably, in step S7, the rotation speed of the dry powder mixer is 80 rpm.

[0024] Preferably, in step S8, the disc inclination angle of the disc granulator is 45-60°, and the rotation speed is 40-60 rpm.

[0025] Preferably, in step S11, the super hydrophobic coating is one of a silane emulsion and a modified hydrophobic nano-silica solution.

[0026] Preferably, during the curing process of step S12, the slag undergoes pozzolanic action, and its chemical expression is:

[0027] xCa(OH)2+Al2O3+(n-1)H2O→xCaO·Al2O3·nH2O

[0028] xCa(OH)2+SiO2+(n-1)H2O→xCaO·SiO2·nH2O

[0029] xCaO·SiO2·nH2O+CaSO4+yH2O→AFt.

[0030] Preferably, the chemical components of the sinter-free ceramsite include shell powder, slag, fly ash, carbide slag, sludge, sodium carbonate and titanium dioxide, and the slag is S95 grade.

[0031] Preferably, the components of the sinter-free expanded clay are: 17-30% by mass of shell powder, 10-18% by mass of slag, 25-35% by mass of fly ash, 16-22% by mass of sludge, 10-20% by mass of carbide slag and 1-2% by mass of titanium dioxide.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] 1. The present invention uses shell powder, slag, carbide slag, fly ash, sludge and titanium dioxide as raw materials, wherein slag and shell powder are used as matrix raw materials, shell powder provides a large amount of calcium source and increases the initial curing temperature of ceramsite, and the increased specific surface area of ​​shells after calcination promotes the adsorption function of ceramsite; carbide slag, waste incineration fly ash and sodium silicate are used as stimulants; the small density and light weight of waste incineration fly ash provide the necessary conditions for preparing ceramsite; the supernatant of carbide slag is used as an auxiliary stimulant; the interior and surface of ceramsite are anti-radiation treated by titanium dioxide and anti-radiation coating to improve the high reflectivity of ceramsite; the hydrophobic coating and nano-scale micro-protrusion structure have a self-cleaning effect, ensure the stable performance of ceramsite, and prevent dust and stains from contaminating the surface of ceramsite; sludge is used as an adsorbent to give the ceramsite an adsorption function.

[0034] 2. The present invention activates slag and shell powder by physical activation, saline-alkali activation and thermal activation to prepare high-strength sinter-free ceramsite. Granulated blast furnace slag has low activity. When the slag contacts water, a layer of impermeable aluminum silicate film is immediately formed on the surface of the particles, which prevents its further hydration. Through physical activation, grinding blast furnace slag increases the specific surface area of ​​blast furnace slag and reduces the diffusion distance of the mass transfer process during the hydration reaction, thereby improving the hydration activity. Fly ash and carbide slag provide a saline-alkali environment for slag, accelerate the disintegration of slag glass, and are conducive to the formation of stable hydration products and their network space structure, forming C-(A)-SH gel, hydrated calcium chloroaluminate and calcium aluminate. Increasing the curing temperature can stimulate the activity of slag and maximize its strength.

[0035] 3. The present invention improves the reflectivity of ultraviolet light, visible light and near infrared light through the composite structure. Among them, titanium dioxide has a high reflectivity for visible light, and the specially made coating has a high reflectivity for ultraviolet light and near infrared light.

[0036] 4. The present invention has the performance of solidifying heavy metals and adsorbing phosphates. Among them, ettringite can react chemically with heavy metals to chemically precipitate heavy metals, and C-(A)-SH gel can also solidify heavy metals by physical encapsulation, chemical precipitation and ion adsorption. It hinders the leaching of heavy metals and ensures the excellent performance of sinter-free ceramsite, such as safety and environmental protection.

[0037] 5. The particle size of the ceramsite prepared by the present invention is 5-10 mm, and the cylinder pressure strength can reach above 10 MPa, which can realize the utilization of hazardous solid waste and the environmentally friendly production of high-quality ceramsite. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a schematic flow chart of a method for preparing sintering-free high-reflectivity ceramsite with solidified heavy metals according to the present invention;

[0039] Figure 2 It is a schematic diagram of the cylinder compressive strength of the sinter-free ceramsite prepared in the method for preparing the sinter-free high-reflectivity ceramsite with solidified heavy metals of the present invention;

[0040] Figure 3 It is a schematic diagram of the reflectivity of the sinter-free ceramsite prepared in the method for preparing the sinter-free high-reflectivity ceramsite with solidified heavy metals of the present invention;

[0041] Figure 4 The present invention is a schematic diagram of the adsorption and phosphorus removal of the unsintered ceramsite prepared in the method for preparing the unsintered high-reflectivity ceramsite with solidified heavy metals. DETAILED DESCRIPTION

[0042] In order to fully describe the technical content, structural features, objectives and effects of the present invention, the following will be described in detail with reference to the accompanying drawings.

[0043] In a preferred embodiment of the present invention, the chemical composition of the unsintered ceramsite includes shell powder, slag, fly ash, carbide slag, sludge, sodium carbonate and titanium dioxide, wherein the slag is S95 grade. The components of the unsintered ceramsite are: the mass percentage of shell powder is 17-30%, the mass percentage of slag is 10-18%, the mass percentage of fly ash is 25-35%, the mass percentage of sludge is 16-22%, the mass percentage of carbide slag is 10-20% and the mass percentage of titanium dioxide is 1-2%. Slag, shell powder, sludge, carbide slag and fly ash are used as raw materials, a mixed solution of sodium carbonate and the upper clear liquid of carbide slag is used as a granulation solution, carbide slag and fly ash are used as alkaline activators, and sludge is used as an adsorbent. In a high temperature and high humidity atmosphere, sintering-free, high-adsorbability and high-strength ceramsite is prepared. The mechanical properties of the sintering-free ceramsite are adjusted by adjusting the working parameters of the granulation disk and the steam curing system. Ceramic ceramsite with a particle size of 5mm-10mm and a compressive strength of 10MPa is prepared, which can realize the recycling of hazardous solid waste and the safe use of ceramsite. Therefore, the preparation method of sintering-free high-reflectivity ceramsite with solidified heavy metals, such as Figure 1 As shown, the specific implementation steps are as follows:

[0044] S1. The carbide slag slurry is placed and separated into layers to obtain a carbide slag lower slurry and a carbide slag upper clear liquid.

[0045] S2. The lower slurry of the carbide slag obtained in step S1 is placed in a drying oven at a temperature of 50-60°C and dried to constant weight, and ground with a ball mill to obtain carbide slag powder; the carbide slag supernatant obtained in step S1 is dried in the sun and concentrated to obtain a carbide slag supernatant with precipitated crystals.

[0046] S3, adding 0.1 mol / L sodium carbonate solution into the carbide slag supernatant with precipitated crystals obtained in step S2 to obtain a mixed solution.

[0047] Specifically, sodium carbonate promotes the dissolution of OH- in the supernatant of carbide slag where crystals are precipitated. The specific chemical formula is: Na2CO3+Ca(OH)2→2NaOH+CaCO3

[0048] 6NaOH+2H2O+4CaCO3→3Ca(OH)2+Na2Ca(CO3)·2H2O+2Na2CO3.

[0049] S4. Place the sludge in a drying oven at a temperature of 50-60°C and dry it to constant weight, grind it in a ball mill for 20 minutes, and pass it through a 200-mesh square hole sieve to obtain sludge powder.

[0050] S5. Place the shells in a drying oven at 60°C and dry them to constant weight, and grind them in a ball mill for 20 minutes to obtain shell powder.

[0051] S6. Place the shell powder obtained in step S5 into a muffle furnace at a temperature of 1000-1200° C. and calcine to obtain calcined shell powder.

[0052] S7. Place slag, fly ash, carbide slag powder, sludge powder, calcined shell powder and titanium dioxide in a dry powder mixer at a rotation speed of 80 rpm in sequence, and stir for 20 minutes to obtain a uniformly mixed dry powder mixture.

[0053] S8, first take a certain amount of the dry powder mixture obtained in step S7 and place it in a disc granulator, and spray the mixed solution obtained in step S3 onto the formed spherical core, and repeat adding the dry powder mixture and spraying the mixed solution into the disc granulator until a spherical raw material with a particle size of 5-10 mm is obtained.

[0054] Furthermore, in order to ensure the formation of spherical raw materials with a particle size of 5-10 mm, the disc inclination angle of the disc granulator needs to be set to 45-60° and the rotation speed to 40-60 rpm.

[0055] S9. Stir polystyrene, vinyl acetate, acetone, water and defoaming agent in a 60° C. water bath for 1-2 hours to obtain an anti-radiation coating.

[0056] S10, placing the spherical raw material obtained in step S8 on a rolling disc, and spraying anti-radiation coating until a raw material ball with a spraying thickness of 0.4-0.8 mm is obtained; however, the anti-radiation coating loses its effect in a humid environment, so the surface of the ceramsite needs to be super-hydrophobic treated.

[0057] S11, prefabricating the raw material ball obtained in step S10 with a nano-scale micro-convex structure, spraying a super-hydrophobic coating, obtaining a super-hydrophobic surface with a spraying thickness of 0.4-0.8 mm on the raw material ball, and standing at room temperature for 24 hours to obtain ceramsite.

[0058] Specifically, the super-hydrophobic coating is one of a silane emulsion and a modified hydrophobic nano-silica solution. The emulsion particles in the super-hydrophobic coating undergo a physical process of demulsification and coating spreading, while the organosilane molecules in the super-hydrophobic coating undergo a chemical process of hydrolysis and polycondensation. Finally, a carbon chain hydrophobic layer connected with silanol groups is formed on the surface of the sludge hydration product, so that the ceramsite is transformed from a hydrophilic property to a hydrophobic property. Among them, the nanoscale micro-convex structure can increase the roughness of the ceramsite surface, and the greater the roughness, the stronger the hydrophobicity.

[0059] S12, placing the ceramsite obtained in step S11 in a water bath curing box at a temperature of 40-70° C. for curing for 8-14 hours, then taking it out and placing it in a curing room for curing to obtain sinter-free ceramsite with solidified heavy metals and high reflectivity.

[0060] Specifically, during the curing process, the slag undergoes pozzolanic action, and its chemical expression is:

[0061] xCa(OH)2+Al2O3+(n-1)H2O→xCaO·Al2O3·nH2O

[0062] xCa(OH)2+SiO2+(n-1)H2O→xCaO·SiO2·nH2O

[0063] xCaO·SiO2·nH2O+CaSO4+yH2O→AFt.

[0064] The present invention solidifies by physical action and chemical bonding. Physical action is mainly to fix heavy metals by intermolecular forces or attraction between opposite charges, and the hydration products in the solidified body (such as CSH gel) encapsulate the insoluble substances containing heavy metals. Chemical bonding is the combination of heavy metals with hydration products in the cement-based material system in the form of chemical bonds, while chemical adsorption is the participation of heavy metals in the formation of hydration products by balancing charges. The formation of insoluble substances refers to the formation of hydroxides or composite hydroxides by heavy metals in an alkaline environment, or the formation of carbonates, sulfates, silicates and oxides containing heavy metals. The structure of the product is a "quasi-crystal" structure composed of cyclic molecular chains. The cyclic molecules are combined to form a closed cavity (cage-like), which can enclose the heavy metals in the cavity or be adsorbed and contained in the polymer, so that the heavy metals are not easy to leach, thereby achieving a solidification effect. However, it is difficult to achieve the leaching standard for soil remediation under high concentrations of heavy metal pollution.

[0065] The following is a further description of a method for preparing a sintering-free high-reflectivity ceramsite with solidified heavy metals according to the present invention in conjunction with an embodiment:

[0066] The specific chemical compositions of sludge, slag, carbide slag, fly ash and shell powder in this specific embodiment are shown in Table 1.

[0067] Table 1 Chemical composition

[0068] Specific embodiment 1:

[0070] S1. The carbide slag slurry is placed and separated into layers to obtain a carbide slag lower slurry and a carbide slag upper clear liquid.

[0071] S2. The lower slurry of the carbide slag obtained in step S1 is placed in a drying oven at a temperature of 55° C. and dried to constant weight, and ground in a ball mill for 25 minutes to obtain carbide slag powder; the carbide slag supernatant obtained in step S1 is dried in the sun and concentrated to obtain a carbide slag supernatant with precipitated crystals.

[0072] S3, adding 0.1 mol / L sodium carbonate solution into the carbide slag supernatant with precipitated crystals obtained in step S2 to obtain a mixed solution.

[0073] S4. Place the sludge in a drying oven at a temperature of 50-60°C and dry it to constant weight, grind it in a ball mill for 20 minutes, and pass it through a 200-mesh square hole sieve to obtain sludge powder.

[0074] S5. Place the shells in a drying oven at 60°C and dry them to constant weight, and grind them in a ball mill for 20 minutes to obtain shell powder.

[0075] S6. Place the shell powder obtained in step S5 into a muffle furnace at a temperature of 1000-1200° C. and calcine to obtain calcined shell powder.

[0076] S7. Place 11% slag by mass, 26% fly ash by mass, 10% carbide slag powder by mass, 22% sludge powder by mass, 30% calcined shell powder by mass and 1% titanium dioxide by mass in a dry powder mixing mixer at a rotation speed of 80 rpm, and stir for 20 minutes to obtain a uniformly mixed dry powder mixture.

[0077] S8. First, take a certain amount of the dry powder mixture obtained in step S7 and place it in a disc granulator with an inclination angle of 30° and a rotation speed of 40 rpm, and spray the mixed solution obtained in step S3 onto the formed spherical cores. Repeat adding the dry powder mixture and spraying the mixed solution into the disc granulator, with the frequency of adding the dry powder mixture and spraying the mixed solution each time being the same, and the solid-liquid ratio being 0.2-0.3, until a spherical raw material with a particle size of 5-10 mm is obtained.

[0078] S9. Stir polystyrene, vinyl acetate, acetone, water and defoaming agent in a 60° C. water bath for 1-2 hours to obtain an anti-radiation coating.

[0079] S10, placing the spherical raw material obtained in step S8 on a rolling disc, and spraying anti-radiation coating, until a raw material ball with a spraying thickness of 0.4 mm is obtained.

[0080] S11, the raw material ball obtained in step S10 is subjected to a prefabricated nanoscale micro-protrusion structure, and a super-hydrophobic coating is sprayed on the raw material ball to obtain a super-hydrophobic surface with a spraying thickness of 0.4 mm, thereby reducing the surface energy of the ceramsite, and the ceramsite is allowed to stand at room temperature for 24 hours to obtain ceramsite.

[0081] S12. Place the ceramsite obtained in step S11 in a water bath curing box at a temperature of 50° C. for curing for 10 hours, then take it out and place it in a curing room at a temperature of 18-24° C. and a relative humidity of not less than 95% for curing for 24 hours to obtain a sinter-free ceramsite sample 1 with solidified heavy metals and high reflectivity.

[0082] This specific embodiment improves the phosphorus adsorption performance of ceramsite by changing the mixing ratio of ceramsite, the rotation speed and inclination angle of the disc granulator and the curing temperature, and increasing the content of sludge powder. The ceramsite obtained by the above specific embodiment has a strength of 8.7 MPa and a reflectivity of 92.2%. Specific embodiment 2:

[0084] S1. The carbide slag slurry is placed and separated into layers to obtain a carbide slag lower slurry and a carbide slag upper clear liquid.

[0085] S2. The lower slurry of the carbide slag obtained in step S1 is placed in a drying oven at a temperature of 55° C. and dried to constant weight, and ground in a ball mill for 25 minutes to obtain carbide slag powder; the carbide slag supernatant obtained in step S1 is dried in the sun and concentrated to obtain a carbide slag supernatant with precipitated crystals.

[0086] S3, adding 0.1 mol / L sodium carbonate solution into the carbide slag supernatant with precipitated crystals obtained in step S2 to obtain a mixed solution.

[0087] S4. Place the sludge in a drying oven at a temperature of 50-60°C and dry it to constant weight, grind it in a ball mill for 20 minutes, and pass it through a 200-mesh square hole sieve to obtain sludge powder.

[0088] S5. Place the shells in a drying oven at 60°C and dry them to constant weight, and grind them in a ball mill for 20 minutes to obtain shell powder.

[0089] S6. Place the shell powder obtained in step S5 into a muffle furnace at a temperature of 1000-1200° C. and calcine to obtain calcined shell powder.

[0090] S7. Place 13.5% by mass of slag, 28% by mass of fly ash, 13% by mass of carbide slag powder, 19% by mass of sludge powder, 25% by mass of calcined shell powder and 1.5% by mass of titanium dioxide in a dry powder mixing mixer at a rotation speed of 80 rpm in sequence, and stir for 20 minutes to obtain a uniformly mixed dry powder mixture.

[0091] S8, first take a certain amount of the dry powder mixture obtained in step S7 and place it in a disc granulator with an inclination angle of 45° and a rotation speed of 50 rpm, and spray the mixed solution obtained in step S3 onto the formed spherical core, repeatedly add the dry powder mixture and spray the mixed solution to the disc granulator, the frequency of adding the dry powder mixture and spraying the mixed solution each time is the same, and the solid-liquid ratio is 0.2-0.3, until a spherical raw material with a particle size of 5-10 mm is obtained.

[0092] S9. Stir polystyrene, vinyl acetate, acetone, water and defoaming agent in a 60° C. water bath for 1-2 hours to obtain an anti-radiation coating.

[0093] S10, placing the spherical raw material obtained in step S8 on a rolling disc, and spraying anti-radiation coating, until a raw material ball with a spraying thickness of 0.6 mm is obtained.

[0094] S11, the raw material ball obtained in step S10 is subjected to a prefabricated nanoscale micro-protrusion structure, and a super-hydrophobic coating is sprayed on the raw material ball to obtain a super-hydrophobic surface with a spraying thickness of 0.6 mm, thereby reducing the surface energy of the ceramsite, and the ceramsite is allowed to stand at room temperature for 24 hours to obtain ceramsite.

[0095] S12. Place the ceramsite obtained in step S11 in a water bath curing box at a temperature of 60° C. for curing for 12 hours, then take it out and place it in a curing room at a temperature of 18-24° C. and a relative humidity of not less than 95% for curing for 24 hours to obtain a sinter-free ceramsite sample 2 with solidified heavy metals and high reflectivity.

[0096] The ceramsite obtained in this specific embodiment has a strength of up to 10.5 MPa and a reflectivity of 96.5%. Specific embodiment 3:

[0098] S1. The carbide slag slurry is placed and separated into layers to obtain a carbide slag lower slurry and a carbide slag upper clear liquid.

[0099] S2. The lower slurry of the carbide slag obtained in step S1 is placed in a drying oven at a temperature of 55° C. and dried to constant weight, and ground in a ball mill for 25 minutes to obtain carbide slag powder; the carbide slag supernatant obtained in step S1 is dried in the sun and concentrated to obtain a carbide slag supernatant with precipitated crystals.

[0100] S3, adding 0.1 mol / L sodium carbonate solution into the carbide slag supernatant with precipitated crystals obtained in step S2 to obtain a mixed solution.

[0101] S4. Place the sludge in a drying oven at a temperature of 50-60°C and dry it to constant weight, grind it in a ball mill for 20 minutes, and pass it through a 200-mesh square hole sieve to obtain sludge powder.

[0102] S5. Place the shells in a drying oven at 60°C and dry them to constant weight, and grind them in a ball mill for 20 minutes to obtain shell powder.

[0103] S6. Place the shell powder obtained in step S5 into a muffle furnace at a temperature of 1000-1200° C. and calcine to obtain calcined shell powder.

[0104] S7. Place 15% by mass of slag, 30% by mass of fly ash, 15% by mass of carbide slag powder, 21% by mass of sludge powder, 17% by mass of calcined shell powder and 2% by mass of titanium dioxide in a dry powder mixing mixer at a rotation speed of 80 rpm in sequence, and stir for 20 minutes to obtain a uniformly mixed dry powder mixture.

[0105] S8, first take a certain amount of the dry powder mixture obtained in step S7 and place it in a disc granulator with an inclination angle of 60° and a rotation speed of 60 rpm, and spray the mixed solution obtained in step S3 onto the formed spherical core, and repeat adding the dry powder mixture and spraying the mixed solution into the disc granulator, with the frequency of adding the dry powder mixture and spraying the mixed solution each time being the same, and the solid-liquid ratio being 0.2-0.3, until a spherical raw material with a particle size of 5-10 mm is obtained.

[0106] S9. Stir polystyrene, vinyl acetate, acetone, water and defoaming agent in a 60° C. water bath for 1-2 hours to obtain an anti-radiation coating.

[0107] S10, placing the spherical raw material obtained in step S8 on a rolling disc, and spraying anti-radiation coating, until a raw material ball with a spraying thickness of 0.8 mm is obtained.

[0108] S11, the raw material ball obtained in step S10 is subjected to a prefabricated nanoscale micro-protrusion structure, and a super-hydrophobic coating is sprayed on the raw material ball to obtain a super-hydrophobic surface with a spraying thickness of 0.8 mm, thereby reducing the surface energy of the ceramsite, and the ceramsite is allowed to stand at room temperature for 24 hours to obtain ceramsite.

[0109] S12. Place the ceramsite obtained in step S11 in a water bath curing box at a temperature of 70° C. for curing for 14 hours, then take it out and place it in a curing room at a temperature of 18-24° C. and a relative humidity of not less than 95% for curing for 24 hours to obtain a sinter-free ceramsite sample 3 with solidified heavy metals and high reflectivity.

[0110] The ceramsite obtained in this specific embodiment has a strength as high as 9.4 MPa and a reflectivity of 95.7%.

[0111] Comparative Example 1:

[0112] S1. The carbide slag slurry is placed and separated into layers to obtain a carbide slag lower slurry and a carbide slag upper clear liquid.

[0113] S2. The lower slurry of the carbide slag obtained in step S1 is placed in a drying oven at a temperature of 55° C. and dried to constant weight, and ground in a ball mill for 25 minutes to obtain carbide slag powder; the carbide slag supernatant obtained in step S1 is dried in the sun and concentrated to obtain a carbide slag supernatant with precipitated crystals.

[0114] S3, adding 0.1 mol / L sodium carbonate solution into the carbide slag supernatant with precipitated crystals obtained in step S2 to obtain a mixed solution.

[0115] S4. Place the sludge in a drying oven at a temperature of 50-60°C and dry it to constant weight, grind it in a ball mill for 20 minutes, and pass it through a 200-mesh square hole sieve to obtain sludge powder.

[0116] S5. Place the shells in a drying oven at 60°C and dry them to constant weight, and grind them in a ball mill for 20 minutes to obtain shell powder.

[0117] S6. Place the shell powder obtained in step S5 into a muffle furnace at a temperature of 1000-1200° C. and calcine to obtain calcined shell powder.

[0118] S7. Place 15% by mass of slag, 28% by mass of fly ash, 13% by mass of carbide slag powder, 19% by mass of sludge powder, 26% by mass of calcined shell powder and 2% by mass of titanium dioxide in a dry powder mixing mixer at a rotation speed of 80 rpm in sequence, and stir for 20 minutes to obtain a uniformly mixed dry powder mixture.

[0119] S8, first take a certain amount of the dry powder mixture obtained in step S7 and place it in a disc granulator with an inclination angle of 45° and a rotation speed of 50 rpm, and spray the mixed solution obtained in step S3 onto the formed spherical core, repeatedly add the dry powder mixture and spray the mixed solution to the disc granulator, the frequency of adding the dry powder mixture and spraying the mixed solution each time is the same, and the solid-liquid ratio is 0.2-0.3, until a spherical raw material with a particle size of 5-10 mm is obtained.

[0120] S9. Stir polystyrene, vinyl acetate, acetone, water and defoaming agent in a 60° C. water bath for 1-2 hours to obtain an anti-radiation coating.

[0121] S10, placing the spherical raw material obtained in step S8 on a rolling disc, and spraying anti-radiation coating, until a raw material ball with a spraying thickness of 0.8 mm is obtained.

[0122] S11, the raw material ball obtained in step S10 is subjected to a prefabricated nanoscale micro-protrusion structure, and a super-hydrophobic coating is sprayed on the raw material ball to obtain a super-hydrophobic surface with a spraying thickness of 0.8 mm, thereby reducing the surface energy of the ceramsite, and the ceramsite is allowed to stand at room temperature for 24 hours to obtain ceramsite.

[0123] S12. Place the ceramsite obtained in step S11 in a water bath curing box at a temperature of 70° C. for curing for 14 hours, then take it out and place it in a curing room at a temperature of 18-24° C. and a relative humidity of not less than 95% for curing for 24 hours to obtain a comparative sintering-free ceramsite sample 1 with solidified heavy metals and reflectivity.

[0124] Comparative Example 2:

[0125] S1. The carbide slag slurry is placed and separated into layers to obtain a carbide slag lower slurry and a carbide slag upper clear liquid.

[0126] S2. The lower slurry of the carbide slag obtained in step S1 is placed in a drying oven at a temperature of 55° C. and dried to constant weight, and ground in a ball mill for 25 minutes to obtain carbide slag powder; the carbide slag supernatant obtained in step S1 is dried in the sun and concentrated to obtain a carbide slag supernatant with precipitated crystals.

[0127] S3, adding 0.1 mol / L sodium carbonate solution into the carbide slag supernatant with precipitated crystals obtained in step S2 to obtain a mixed solution.

[0128] S4. Place the sludge in a drying oven at a temperature of 50-60°C and dry it to constant weight, grind it in a ball mill for 20 minutes, and pass it through a 200-mesh square hole sieve to obtain sludge powder.

[0129] S5. Place the shells in a drying oven at 60°C and dry them to constant weight, and grind them in a ball mill for 20 minutes to obtain shell powder.

[0130] S6. Place the shell powder obtained in step S5 into a muffle furnace at a temperature of 1000-1200° C. and calcine to obtain calcined shell powder.

[0131] S7. Place 20% by mass of slag, 20% by mass of fly ash, 20% by mass of carbide slag powder and 40% by mass of calcined shell powder in a dry powder mixing mixer at a rotation speed of 80 rpm in sequence, and stir for 20 minutes to obtain a uniformly mixed dry powder mixture.

[0132] S8. First, take a certain amount of the dry powder mixture obtained in step S7 and place it in a disc granulator with an inclination angle of 60° and a rotation speed of 50 rpm, and spray the mixed solution obtained in step S3 onto the formed spherical cores. Repeat adding the dry powder mixture and spraying the mixed solution into the disc granulator, with the frequency of adding the dry powder mixture and spraying the mixed solution each time being the same, and the solid-liquid ratio being 0.2-0.3, until a spherical raw material with a particle size of 5-10 mm is obtained.

[0133] S9. Stir polystyrene, vinyl acetate, acetone, water and defoaming agent in a 60° C. water bath for 1-2 hours to obtain an anti-radiation coating.

[0134] S10, placing the spherical raw material obtained in step S8 on a rolling disc, and spraying anti-radiation coating, until a raw material ball with a spraying thickness of 0.8 mm is obtained.

[0135] S11, the raw material ball obtained in step S10 is subjected to a prefabricated nanoscale micro-protrusion structure, and a super-hydrophobic coating is sprayed on the raw material ball to obtain a super-hydrophobic surface with a spraying thickness of 0.8 mm, thereby reducing the surface energy of the ceramsite, and the ceramsite is allowed to stand at room temperature for 24 hours to obtain ceramsite.

[0136] S12. Place the ceramsite obtained in step S11 in a water bath curing box at a temperature of 60° C. for curing for 12 hours, then take it out and place it in a curing room at a temperature of 18-24° C. and a relative humidity of not less than 95% for curing for 24 hours to obtain a comparative sintering-free ceramsite sample 2 with solidified heavy metals and reflectivity.

[0137] Through the above specific embodiments and comparative examples, the test results can be obtained as shown in Table 2.

[0138] Table 2 Characteristics of sinter-free ceramsite samples

[0139]

[0140] The influence of the composition of ceramsite on its strength Figure 2 As shown, the cylinder compression strength of ceramsite made of shell powder is higher, and the strength of sample 1, sample 2 and sample 3 is increased by 29.85%, 56.72% and 40.30% respectively compared with the comparative sample 1, and the strength of sample 1, sample 2 and sample 3 is increased by 31.82%, 59.09% and 42.42% respectively compared with the comparative sample 2, indicating that shell powder is beneficial to improving the cylinder compression strength of ceramsite. The content of slag and carbide slag powder is increased in specific embodiment 1, specific embodiment 2 and specific embodiment 3. The results show that the appropriate content of slag and carbide slag is beneficial to improving the strength. When the content of carbide slag is too large, the strength development is inhibited, which has an adverse effect on the strength. Excessive carbide slag inhibits the polymerization reaction of solid waste cementitious materials and inhibits the generation of C-(A)-SH.

[0141] The influence of the composition of ceramsite on the reflectivity of light is as follows Figure 3 As shown, by adding different amounts of titanium dioxide, the reflectivity of ceramsite is improved. The reflectivity of samples 1, 2 and 3 is increased by 22.6%, 28.32% and 27.26% compared with that of comparative sample 1, and the reflectivity of samples 1, 2 and 3 is increased by 17.75%, 23.24% and 22.22% compared with that of comparative sample 2. This indicates that the reflectivity of ceramsite increases with the increase of titanium dioxide content, and titanium dioxide has a significant effect on improving the reflectivity of ceramsite, but excessive titanium dioxide reduces the reflectivity of ceramsite.

[0142] Effect of ceramsite material composition on phosphorus adsorption Figure 4As shown, increasing the sludge content increases the average phosphorus adsorption rate, and excessive sludge affects the microscopic results of ceramsite, affects the pore composition, and thus affects the phosphorus adsorption amount. Table 2 shows the values ​​of heavy metal leaching content of ceramsite produced in specific embodiments, and the values ​​all meet the requirements. Therefore, the ceramsite obtained by the method of the present invention has high strength, high reflectivity, high phosphorus adsorption and the performance of solidifying heavy metals.

[0143] The embodiments described above are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing sinter-free high-reflectivity ceramsite with solidified heavy metals, characterized in that: The specific implementation steps include: S1, subjecting the carbide slag slurry to static stratification to obtain a carbide slag lower slurry and a carbide slag upper clear liquid; S2, placing the lower slurry of the carbide slag obtained in step S1 into a drying oven at a temperature of 50-60° C. to dry to constant weight, and grinding it with a ball mill to obtain carbide slag powder; drying and concentrating the carbide slag supernatant obtained in step S1 to obtain a carbide slag supernatant with precipitated crystals; S3, adding 0.1 mol / L sodium carbonate solution into the carbide slag supernatant with precipitated crystals obtained in step S2 to obtain a mixed solution; S4, placing the sludge in a drying oven at a temperature of 50-60°C to dry to constant weight, grinding it with a ball mill and passing it through a square hole sieve to obtain sludge powder; S5, placing the shells in a drying oven at a temperature of 60° C. to dry to constant weight, and grinding them with a ball mill to obtain shell powder; S6, placing the shell powder obtained in step S5 into a muffle furnace at a temperature of 1000-1200° C. for calcination to obtain calcined shell powder; S7, placing slag, fly ash, carbide slag powder, sludge powder, calcined shell powder and titanium dioxide in a dry powder mixer in sequence to obtain a uniformly mixed dry powder mixture; S8, placing the dry powder mixture obtained in step S7 in a disc granulator, and spraying the mixed solution obtained in step S3 onto the formed spherical core, and repeatedly adding the dry powder mixture to the disc granulator and spraying the mixed solution until a spherical raw material with a particle size of 5-10 mm is obtained; S9, stirring polystyrene, vinyl acetate, acetone, water and defoaming agent in a 60° C. water bath for 1-2 hours to obtain an anti-radiation coating; S10, placing the spherical raw material obtained in step S8 on a rolling disc, and spraying anti-radiation coating until a raw material ball with a spraying thickness of 0.4-0.8 mm is obtained; S11, the raw material ball obtained in step S10 is subjected to a prefabricated nanoscale micro-convex structure, and a super-hydrophobic coating is sprayed on the raw material ball to obtain a super-hydrophobic surface with a spraying thickness of 0.4-0.8 mm, and the raw material ball is allowed to stand at room temperature for 24 hours to obtain ceramsite; S12, placing the ceramsite obtained in step S11 in a water bath curing box at a temperature of 40-70° C. for curing for 8-14 hours, then taking it out and placing it in a curing room for curing to obtain sintering-free high-reflectivity ceramsite with solidified heavy metals; The chemical composition of the sinter-free expanded clay includes shell powder, slag, fly ash, carbide slag, sludge, sodium carbonate and titanium dioxide, and the slag is of S95 grade; the components of the sinter-free expanded clay are: the mass percentage of calcined shell powder is 17-30%, the mass percentage of slag is 10-18%, the mass percentage of fly ash is 25-35%, the mass percentage of sludge is 16-22%, the mass percentage of carbide slag is 10-20% and the mass percentage of titanium dioxide is 1-2%.

2. The method for preparing the sinter-free high-reflectivity ceramsite with solidified heavy metal according to claim 1, characterized in that: In step S3, the sodium carbonate in the sodium carbonate solution promotes the dissolution of OH-, and the specific chemical expression is: Na2CO3+Ca(OH)2→2NaOH+CaCO3 6NaOH+2H2O+4CaCO3→3Ca(OH)2+Na2Ca(CO3)·2H2O+2Na2CO3.

3. The method for preparing the sinter-free high-reflectivity ceramsite with solidified heavy metal according to claim 1, characterized in that: In step S7, the rotation speed of the dry powder mixing and stirring machine is 80 rpm.

4. The method for preparing the sinter-free high-reflectivity ceramsite with solidified heavy metal according to claim 1, characterized in that: In step S8, the disc inclination angle of the disc granulator is 45-60°, and the rotation speed is 40-60 rpm.

5. The method for preparing the sinter-free high-reflectivity ceramsite with solidified heavy metal according to claim 1, characterized in that: In step S11, the super hydrophobic coating is one of a silane emulsion and a modified hydrophobic nano-silica solution.

Citation Information

Patent Citations

  • Shell and sludge sintered ceramsite and preparation method thereof

    CN108892479A

  • Unfired ceramsite processed by utilizing red mud, fly ash, iron tailings and carbide slag solid waste as well as preparation method and application of unfired ceramsite

    CN113912376A

  • Ceramic granules having high reflectivity and preperation method for the same

    US20170174575A1